A Case Study of Music Museum Research-Based Learning Practice from the Perspective of Music Education - Lili Li (Education Research on Study Tours and Practice, 2026)
The new era of aesthetic education reform calls for a three-dimensional system integrating classroom teaching, social practice, and cultural immersion. As a professional platform carrying musical artifacts, historical materials, and regional music culture, music museums hold significant educational value for research-based learning. This study takes the museum-school collaborative research project at Harbin Music Museum as a practical vehicle, constructing a four-stage closed-loop practice system consisting of pre-study preparation, immersive research, hands-on experience, and post-study extension. The results show that this model effectively overcomes the limitations of traditional music education, which emphasizes theory over practice and classroom over experience, thereby enhancing students’ aesthetic perception, cultural heritage awareness, and creative abilities. In response to issues such as insufficient systematization of the curriculum and limited depth of outcome transformation, optimization strategies are proposed, including building a tiered curriculum system, deepening museum-school integration, innovating research formats, and cultivating dual-qualified teaching teams. This study provides a replicable paradigm for transforming music museum research-based learning from periodic activities into regular courses.